Pengaruh Kepemimpinan Dan Pengawasan Terhadap Disiplin Kerja Karyawan Pada PT. Fatarindo Cemerlang Ccod Singaraja - Winaya Purwanti (Cakrawala Akuntansi & Manajemen, 2021)
The study aims to examine the effect of (1) leadership and supervision of job discipline, (2) leadership of job discipline, (3) supervision of job discipline. The population in this are all employee who work at PT. Fatarindo Cemerlang CCOD Singaraja with 38 employee. Based on the characteristics of the problem under study, this study uses a causal quantitative research design. The data analysis technique used is multiple linier regression analysis techniques. The results showed that (1) leadership and supervision significantly affect job discipline, (2) leadership has a significant impact on job discipline, (3) supervision has a significant impact on job discipline.